Implikasi Etika Bisnis Dalam Perdagangan Internasional: Tinjauan Terhadap Kegiatan Ekspor Dan Impor - Fauzan Habib; Hendra Ibrahim (Journal of Islamic Economics and Finance, 2024)
International trade has become an increasingly important activity in the global economy. The implications of these business ethics include work standards and human rights, the environment, corruption, legal bankruptcy, transparency, and accountability, as well as sustainable social and environmental principles. This study aims to review the implications of business ethics in international trade. This study used a descriptive analytical method and data were obtained from related literature sources. The results of the study show that companies are involved in export and import activities in the country. The business ethics implications must be fulfilled to encourage responsible, sustainable, and beneficial international trade for all parties involved in international trade activities.